ANÁLISIS DE CALIDAD DEL SERVICIO QUE PRESTA EL HOTEL LIBERTADOR DE LA CIUDAD DE LOJA - Guacho Lamar, Viviana Isabel (2019)
The present research study called "Quality Analysis of the service provided by the Hotel Libertador of the city of Loja.", Arises from the need to improve the quality of service offered to the tourist or the final consumer, to train their staff to improve the services of the establishments and increase the tourist activity within the city. Therefore, the manager, collaborators and clients were selected as research subjects. The Hotel Libertador is located in the city of Loja, a company made up of shareholders, one of the pioneer companies with 28 years of experience in providing hotel services, with lodging, restaurant and complementary services. It has led as one of the best hotels in the southern region of Ecuador, combining the comfort of an excellent hotel with quality Ecuadorian hospitality as the establishment's commitment is to provide quality service at the most convenient rates. This research is made up of the general objective called "Analysis of Quality of Service provided by the Hotel Libertador of the City of Loja" and its specific objectives that contributed with information for the development of the research are: Diagnose the current situation of the "Hotel Libertador", Evaluate the quality of the service offered by the" Hotel Libertador "and propose strategies to improve the quality of the" Hotel Libertador "service. For the development of the first objective was developed a diagnostic file that contains general data of the company, the regulations of the tourist company and requirements of the infrastructure, diagnosis made to the general manager, to collect more Information two interviews were prepared, one focused to the employees of the hotel and another to the manager of the company with the aim of collecting more specific information, then proceeded to elaborate the matrix SWOT, but focused to the internal part of the hotel, ie the Strengths and weaknesses of the establishment. For the development of the second objective was formed based on the Servqual method, which allows for this process to measure the expectations and perceptions that the customer has about the service received, within five dimensions (tangible elements, reliability, Sensitivity, safety and empathy), a method used for the elaboration of the surveys to be applied. Once analyzed the information of the surveys, it proceeded to elaborate the second part of the SWOT, focused on the external partie, in the opportunities and threats of the hotel, to later cross them and to form the strategic SWOT that will help to raise the Improvement strategies for the company. Finally, for the fulfillment of the third objective, the strategies were raised to help the hotel to improve its quality of service, where a painting was developed for each strategy, explaining in detail what the strategy consists of, its characteristics, policies, Indicators and their goals. 5 On the other hand within the results it is verified that the hotel complies with most of the diagnostic file, but still has a deficiency within the regulation because it does not have a wheelchair ramp and a braille system to provide facilities necessary to pay attention to people with disabilities. In terms of infrastructure, the hotel does not have soundproofed rooms, with a complete personal hygiene kit, requirements established by the MINTUR within the tourist accommodation card. As for the surveys, it is verified that a certain number of clients is not satisfied at 100% with the services received, in the service of restaurant they excel the music and the decoration; Lodging Service The following are highlighted: ventilation of the room and fulfillment of the services offered and finally in the complementary service it focused on the area of swimming pool, service more used in the time that the surveys were applied, Obtaining the following indicators that have deficiencies: modern-looking equipment and physical installations, image of the personnel of the establishment and fulfillment-solution to its drawbacks. On the other hand within the results it is verified that the hotel complies with most of the diagnostic file, but still has a deficiency within the regulation because it does not have a wheelchair ramp and a braille system to provide facilities necessary to pay attention to People with disabilities. In terms of infrastructure, the hotel does not have soundproofed rooms, with a complete personal hygiene kit, requirements established by the MINTUR within the tourist accommodation card. As for the surveys, it is verified that a certain number of clients is not satisfied at 100% with the services received, in the service of restaurant they excel the music and the decoration; Lodging Service The Following are highlighted: ventilation of the room and fulfillment of the services offered and finally in the complementary service it focused on the area of swimming pool, service more used in the time that the surveys were applied, Obtaining the Following indicators that have deficiencies: modern-looking equipment and physical installations, image of the personnel of the establishment and fulfillment-solution to its drawbacks.